Tumor-associated macrophage expression in colorectal adenomas and carcinomas: relationship to Helicobacter pylori infection - Wang, Wenming; Zhu, Yueyong; Zhu, Yunchao; Wang, Jin (Frontiers in Oncology, 2025)
ObjectiveThis study investigated the association between Helicobacter pylori (H. pylori) infection and the expression of CD163+ and CD86+ tumor-associated macrophages (TAMs) in colorectal adenoma (CRA) and colorectal cancer (CRC) tissues.MethodsImmunohistochemistry (IHC) was used to evaluate the expression of CD163+ and CD86+ TAMs isolated from colorectal tissues, Multiplex immunofluorescence (mIF) co-staining was employed to identify CD68+CD163+ and CD68+CD86+ TAMs, and the 14C-urea breath test (UBT) was used to detect H.pylori infection.ResultsThe progression of colorectal lesions was significantly associated with increased expression of CD163+ and CD86+ TAMs, as well as H.pylori infection (all P < 0.05). The expression of CD163+ and CD86+ TAMs were positively correlated with each other and with the severity of colorectal lesions (all P < 0.001). Patients with H.pylori infection exhibited significantly higher expression of both TAM subsets compared with non-infected individuals (all P < 0.05). Multiple linear regression analysis showed that in colorectal adenomas measuring ≥ 1 cm, expression of CD163+ and CD86+ TAM was significantly greater than in adenomas <1 cm (P < 0.05), Expression of CD163+ TAM was notably higher in obese patients with CRC. Multiplex immunofluorescence (mIF) quantification revealed significantly increased densities of both CD68+CD86+ and CD68+CD163+ TAMs, and a higher CD68+CD163+/CD68+CD86+ ratio in colorectal cancer (CRC) (all P < 0.001).ConclusionsThe expression of CD68+CD163+ and CD68+CD86+ TAMs change dynamically with the progression of colorectal lesions. These changes are influenced by H.pylori infection, adenoma size, tumor differentiation, and patient metabolic status.